Pengaruh Motivasi Berafiliasi dan Komitmen Afektif terhadap Kinerja Pegawai Badan Pendapatan Daerah Kabupaten Labuhanbatu - Muhammad Syahrul Ramadhan; Ade Parlaungan Nasution; Zulkarnain Nasution (J-MAS (Jurnal Manajemen dan Sains), 2022)
The Regional Revenue Agency of Labuhanbatu Regency can improve employee performance by increasing an important component of management, namely human resources (HR), which includes affiliation motivation and affective commitment. Affiliation motivation and affective commitment can be decisive if the drive to achieve organizational success is implemented with a strong belief to follow all organizational values. This study aims to analyze the effect of affiliation motivation and affective commitment on employee performance at the Regional Revenue Agency of Labuhanbatu Regency. The population in this study amounted to 90 people. The sampling technique used was saturated sampling, so the sample size in this study was 90 people. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y=1,838+0,363X1+0,812X2. In the partial test (t test) the regression coefficient of the affiliated motivation variable (X1) obtained a t value of 2.416 > t table 1.987 which means that the affiliated motivation variable has a positive and significant effect on the employee performance variable with a significant value of 0.018 < 0.05. The regression coefficient for the affective commitment variable (X2) obtained a t-count value of 5.394 > t-table 1.987, which means that the affective commitment variable has a positive and significant effect on the employee performance variable with a significant value of 0.000 <0.05. The results of the F test obtained that the Fcount value of 119,959 > Ftable 3.10 with a significant value of 0.000 <0.05, which means that the affiliation motivation variable and affective commitment simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test show that the affiliation motivation variable and affective commitment have an influence of 73.4% on the employee performance variable, while the remaining 26.6% is influenced by other variables outside of this study.